Hf isotope compositions of U.S. Geological survey reference materials - Weis, D; Kieffer, B; Hanano, D; Silva, I; Barling, J; Pretorius, W; Maerschalk, C; Mattielli, N (2007)
A systematic multi-isotopic and trace element characterization of U.S. Geological Survey reference materials has been carried out at the Pacific Centre for Isotopic and Geochemical Research, University of British Columbia. Values of 176Hf/177Hf are recommended for the following reference materials (mean ±2 SD): G-2: 0.282523 ± 6; G-3: 0.282518 ± 1; GSP-2: 0.281949 ± 8; RGM-1: 0.283017 ± 13; STM-1: 0.283019 ± 12; STM-2: 0.283021 ± 5; BCR-1: 0.282875 ± 8; BCR-2: 0.282870 ± 8; BHVO-1: 0.283106 ± 12; BHVO-2: 0.283105 ± 11; AGV-1: 0.282979 ± 6; and AGV-2: 0.282984 ± 9. Reproducibility is better than 50 ppm for the granitoid compositions and better than 40 ppm for the basaltic/andesitic compositions. For the isotopic analyses acquired early in this project on glass columns, Hf isotopic analyses from several of the reference materials were significantly less reproducible than Nd and Sr isotopic analyses determined from the same sample dissolution. The 176Hf/ 177Hf ratios for relatively radiogenic compositions (BCR-1, 2; BHVO-1, 2; RGM-1) were shifted systematically toward lower values by 100-150 ppm when a borosilicate primary column was used. Although systematic, the shift for felsic compositions was generally within analytical error, except for GSP-2, which has a very low Hf isotopic ratio, where the shift was to higher 176Hf/177. Trace element and isotopic characterization of the borosilicate glass column, borosilicate frits, and quartz columns reveals extremely variable levels of trace elements. The 176Hf/177 ratios for these materials are very unradiogenic (borosilicate glass <0.28220; frit = 0.28193 ± 4). The borosilicate frit material appears to be the most variable in elemental concentration and isotopic composition. The quartz material has very low levels (